Ahklak dan Relasi: Hubungan antara syariat, theosofi, hakikat, dan mahabbah, dan perlunya keselarasan antara syariat dengan theosofi - mahfudhah#, inayati; Novandra, Fasha Karen; Al Farez, Dhimas Ahmad (Maliki Interdisciplinary Journal, 2026)
Modern societal shifts toward materialism often trigger severe moral crises and spiritual emptiness, reducing religious practices to mere formalistic rituals. This study aims to deeply examine the interconnectedness of sharia, morality, theosophy, essence, and mahabbah as a holistic solution to this contemporary issue. Employing a qualitative approach through literature research, data were gathered from relevant classic and contemporary scholarly sources and analyzed descriptively. The findings demonstrate that sharia functions as an outward behavioral guideline, while theosophy deepens the internal spiritual relationship between humans and God. The harmony of these aspects shapes genuine morality, uncovers the true spiritual essence of worship, and culminates in mahabbah—the ultimate love for Allah. This study concludes that a balanced integration of both outward and inward dimensions is essential to fostering a well-rounded, moderate Muslim personality capable of navigating modern life meaningfully.